The Effect of Basic Life Support (BHD) Counseling on the Level of Knowledge of Grade XI Students at SMA Santo Thomas 1 Medan 2024 - Zebua, Ayin Lidia Srinawan; Pane, Jagentar P.; Barus, Mardiati (Mata Pena Madani, 2025)
Basic Life Support (BHD) is a series of first aid services carried out to help anyone who experiences respiratory and cardiac arrest. Emergencies can happen anytime, anywhere, and to anyone. This study aims to determine the influence of counseling about BHD on the knowledge of grade XI students at SMA Santo Thomas 1 Medan. This design uses a pre-experimental design with a one-group pretest-posttest design approach. The population in this study are 432 students in grade XI of SMA Santo Thomas 1 Medan, in sampling using Probability sampling with a systematic sampling technique with a sample of 36 people. Data analysis using the Paired T Test. The results of the analysis of the knowledge of Essential Life Support (BHD) in grade XI students before being given the intervention had a score of less than 23 people (63.9%) and 13 people (36.1%), after being given the intervention only 3 people (8.3%), good 33 people (91.7%). So that there is an influence of counseling on basic living stones (BHD) on the level of knowledge of grade XI students, a p-value of 0.001 0.05 is obtained. The results of this study provide input to the students of SMA Santo Thomas 1 Medan in order to be able to hold training on the handling of basic living stones (BHD) for students of SMA Santo Thomas 1 Medan.